2005
DOI: 10.1016/j.jvs.2005.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of color duplex ultrasound measurement in the estimation of internal carotid artery stenosis: A systematic review and meta-analysis

Abstract: Clinicians need to be aware of the limitations of duplex ultrasound scanning when making management decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
173
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(185 citation statements)
references
References 64 publications
1
173
0
11
Order By: Relevance
“…The authors found that carotid duplex ultrasonography had an estimated sensitivity of 86% and a specificity of 87% for detecting carotid artery stenosis of 70%-99%. 54 In a meta-analysis by Jahromi and colleagues, 29 the authors reported comparable results for sensitivity and specificity. Using their analysis, a sensitivity of 94% was estimated, as was a specificity of 92% for carotid artery stenosis of 60% or greater.…”
Section: Diagnostic Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors found that carotid duplex ultrasonography had an estimated sensitivity of 86% and a specificity of 87% for detecting carotid artery stenosis of 70%-99%. 54 In a meta-analysis by Jahromi and colleagues, 29 the authors reported comparable results for sensitivity and specificity. Using their analysis, a sensitivity of 94% was estimated, as was a specificity of 92% for carotid artery stenosis of 60% or greater.…”
Section: Diagnostic Studiesmentioning
confidence: 95%
“…Using their analysis, a sensitivity of 94% was estimated, as was a specificity of 92% for carotid artery stenosis of 60% or greater. 29,72 The reliability of carotid artery duplex ultrasonography, however, has significant limitations with important differences in the measurement properties applied by different ultrasound laboratories, which may result in clinically relevant differences.…”
Section: Diagnostic Studiesmentioning
confidence: 99%
“…The evaluation therefore contains information regarding stenosis morphology as well as information regarding the flow velocity measured in cm per second, the peak systolic velocity (PSV) and the end diastolic velocity (EDV) being the most prominent parameters. According to the current literature, a PSV of > 130 cm/sec will be found in more than 50 % of cases of ICA stenosis, whereas a PSV of > 250 cm/ sec and end diastolic velocity of > 120 cm/sec describe more than 70 % of cases of stenosis [61]. Since color-coded duplex ultrasound and spectrum analysis are particularly dependent on the experience of the examiner and the angle of the ultrasound probe, there is a trend toward using alternative methods for stenosis grading in the clinical routine.…”
Section: Color-coded Duplex Sonography For Graduation Of Stenosismentioning
confidence: 98%
“…It is currently indisputable that the accurate grading of internal carotid stenosis can be reliably done by means of ultrasound. There are several studies in which ultrasound has reached excellent sensitivity and specificity values for this purpose as compared to other methods [30]. For exact stenosis quantification, a combination of B-mode imaging, the superimposed color-coded duplex analysis and analysis of the derived Doppler spectrum is used [31] (• ▶ Fig.…”
Section: Color-coded Duplex Sonography For Graduation Of Stenosismentioning
confidence: 99%
“…O seguimento no pós-operatório da ECA associado ao avanço e ao uso mais abrangente dos testes diagnósticos não invasivos, em especial a ultrassonografia com Doppler, proporcionou um aumento no número de diagnóstico de pacientes portadores de reestenose da artéria carótida pós-endarterectomia 3 .…”
Section: Introductionunclassified